Probiotics Reduce Health Care Cost and Societal Impact of Flu-Like Respiratory Tract Infections in the USA: An Economic Modeling Study - Lenoir-Wijnkoop, Irene; Merenstein, Dan; Korchagina, Daria; Broholm, Christa; Sanders, Mary Ellen; Tancredi, Dan (Frontiers in Pharmacology, 2019)
Acute respiratory tract infections (RTIs) of viral origin place a substantial burden on health care resources and society. Randomized controlled trials have shown positive effects of probiotics on clinical outcomes in these commonly occurring RTIs. Two meta-analyses published by the York Health Economics Consortium (YHEC) and Cochrane reported efficacy of probiotics in reducing incidence and duration of RTIs, number of antibiotic courses and days absent from work. The aim of this study was to assess the potential health-economic impact of probiotics on RTI-associated events and expenses in the USA primary care setting. A state-transition microsimulation model reproduced a study population representative of the USA national demographics for age and gender (1/1000 sample). RTI incidence was based on the influenza-like illness outpatient consultation rate reported by CDC FluView. Data on vaccination, on factors that negatively impact RTI outcomes, on resource utilization and on productivity loss were obtained from USA national databases. Analyses were performed for both meta-analyses independently. Outcomes included cost-savings for the health care payer, related to reduced number of RTI episodes, less outpatient consultations and decreased medical prescriptions as well as cost-savings from a broader societal perspective related to productivity loss. The analysis showed that generalized probiotic intake in the USA population for 2017-2018 would have allowed cost-savings for the health care payer of 4.6 million USD based on the YHEC scenario and 373 million USD for the Cochrane scenario, by averting respectively 19 million-54.5 million RTI sick days, compared to no probiotics. Antibiotic prescriptions decreased with 1.39 million-2.16 million courses, whereas absence from work decreased by 3.58 million-4.2 million days when applying the YHEC and Cochrane data respectively. When including productivity loss, total savings for society represented 784 million or 1.4 billion USD for YHEC and Cochrane scenarios, respectively. Subgroup analyses demonstrated an incremental benefit of probiotics in at-risk groups, which might be of relevance for targeted interventions. Sensitivity analyses confirmed the robustness of the model outcomes. Our analysis demonstrated a positive impact of probiotics on the health care and economic burden of flu-like RTIs. Improved disease outcomes translated into considerable cost-savings for both the payer and society.